Designing Business Models through a Combination of BMC and UML Methods at Eiger Adventure Store Bandung - Diva, Fadel; Priyadi, Yudi (Universitas Nusantara PGRI Kediri, 2020)
Eiger Adventure Store Bandung is a company that manufactures outdoor clothing and accessories. The problem with Eiger, related to the lack of activities to educate customers about the difference between original and counterfeit products. Referring to the problems in Eiger, the purpose of this study is to design a Business Model Canvas (BMC), design a business model using the Unified Model Language (UML), create a User Interface visualization through a MockupMockup. The research method used is qualitative through SWOT support. Referring to the BMC of this research, a new business model recommendation has been produced, namely QR Code Scan. This business model has been described through UML and is visualized with Mock-Up. The UML diagram involved, among them, is the Use Case Diagram, which consists of five actors, namely customers, employees, cashiers, admins, and warehouse employees. The actor interacts on four Use Cases, namely choosing a product, QR Code Scan, Database, and payment. The Class Diagram consists of five main classes: customers, employees, cashiers, admins, and warehouse employees. The process contained in the QR Code Scan is a solution to provide education to customers to be able to distinguish genuine or imitation products.